Pendampingan Positive Diviance Pemberian Makanan Tambahan dalam Upaya Penanganan Stunting di Desa Tanjung Agung - Kurniati; Nurfadila; Rosmiati, Meiti; Usviany, Veny (PADMA, 2024)
Bulungan Regency, East Tanjung Palas District, especially in Tanjung Agung Village, there were recorded 24 children suffering from stunting, the majority of which were caused by factors including an unclean environment and lack of knowledge about nutrition that supports children's growth. One solution that can be implemented is the Positive Daviance Program in Providing Supplementary Feeding (PMT). The method used in this program is through the planning stage, implementation stage and program evaluation stage as well as assistance in making PMT and providing a little education to parents of toddlers. Where service members provide monitoring assistance to Mempesona Cadres and Toddler Mothers in the PMT making activity and also provide a little education to parents of toddlers regarding stunting management through Providing Supplementary Food (PMT). This activity aims to help improve the growth and development of children who are already experiencing stunting. The results of the Positive Daviance PMT activity which was carried out for 28 days with 2 weighing evaluations during the gradual increase in body weight. The results of the activity also show that there has been an increase in parents' awareness of children's nutrition, which must be met, namely almost 100%, through activities to educate parents of toddlers so that the handling of stunting, especially in the Tanjung Palas Timus subdistrict in Tanjung Agung Village, can be resolved immediately